Design, analysis, and realization of a magnetic force transmission PM brushless motor. Issue 5 (21st January 2018) - Libing, Jing; Ting, Zhang; Ying, Lin; Jia, Cheng
Abstract : This paper proposes a novel direct‐driving motor that successfully embeds a permanent magnet brushless motor (PMBM) into a concentric magnetic gear (CMG). The PMBM and CMG share a common high‐speed rotor. In order to reduce the flux harmonics and get high torque density, Halbach arrays are employed to arrange the PM's poles on each side of the rotor, which completely makes the internal PMBM field and the external CMG field decoupled and improves the magnetic field characteristic. The results of finite element computation show that the proposed motor with Halbach arrays has over 7.5% higher torque density and that the cogging torque reduces to 1/20 that of a conventional radial magnetization motor; moreover, in the test, the back‐EMF waveform is closer to a sine wave and the three‐phase current waveforms show good agreement between the simulated and experimented results under the same load. The torque ripple is small and the dynamic performance is good. At the same time, the efficiency at the rated point is very close to the experimental one, which validates the effectiveness of the design method for the PMBM in the CMG. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.